Vegetative and reproductive development of Bixa orellana L. based on its propagation - Públio Júnior, Everardes; Nair Hojo Rebouças, Tiyoko; Rebouças São José, Abel; Prado Barreto Públio, Ana Paula; Silva Porto, John (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
Bixa orellana L., also known as achiote, is a shrub native to tropical regions. It has been arousing the interest of the industrial sector due to the film that covers its seeds, which is rich in a reddish carotenoid called bixin. Although, traditionally, it is sexually propagated through seeds, this process can also take place in a vegetative manner. Given the economic and social relevance of this species, the aim of the current study is to assess both the vegetative and reproductive development of achiote plants, based on their propagation process, to help finding the best association between plant growth and early production. The experiment was conducted in a farm, in Porto Seguro City – Bahia State. Treatments were based on two genotypes (A and B), which were multiplied through asexual (plant cutting) and sexual (seeds) reproduction. The experimental design was based on randomized blocks, at 2x2 factorial arrangement, with 5 repetitions and 7 useful plants per plot. The following parameters were assessed at 59, 154, 284, 383, 497, 656 and 840 days after planting: incidence of flowers and/or capsules, stem diameter, plant height and canopy diameter. Collected data were compared to each other through Tukey’s test, at 5% probability level. Asexually propagated treatments were the first to start the reproduction stage, whereas sexually propagated treatments recorded higher vegetative development rate; no difference in vegetative development and in reproductive stage onset was observed between the investigated genotypes.